An organized anarchy? Understanding the role of German cooperation in the construction and export of the dual training model. (11th June 2022) - Fontdevila, Clara; Valiente, Oscar; Schneider, Sebastian
Abstract: The role of German cooperation as a key force behind the worldwide dissemination of dual training is well‐established within the specialized literature. The multilayered and fragmented nature of the German cooperation landscape suggests that German efforts in this area follow a complex and evolving interplay of motivations—yet the rationales behind Germany's bilateral work in the area of technical and vocational education and training (TVET) have rarely been examined in a systematic way. Additionally, existing approaches to the question of aid motivations as provided by economics and international relations scholarship appear to be ill‐suited to understanding the rationales behind Germany's TVET cooperation efforts. Drawing on a combination of document analysis and interviews with key stakeholders, this paper investigates the heterogeneity of drivers and motivations behind German cooperation efforts in the promotion and export of the dual training model and examines the coordination challenges posed by this diversity. The paper finds that German efforts in the international promotion of dual training are driven by at least three analytically distinct rationales that correspond roughly to three differentiated poles within the German policy space—namely, the economic, development and education arenas. The paper also finds that this diversity of motivations poses important coordination challenges—and that, while recent coordination efforts have succeeded in securing some degree of rhetorical consistency, only limited progress has been made in terms of operational coherence.